Analisis Peran Surah Al-Fatihah dalam Pelaksanaan Ibadah Sehari-hari Menurut Mufassir Klasik dan Kontemporer - Azis Rustandi; M. Aufa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study aims to explore the role of Surah Al-Fatihah in the daily worship of Muslims, focusing on the interpretations of the classical scholar Ibn Katsir and the contemporary scholar Wahbah Zuhaili. As the first chapter of the Qur’an, Al-Fatihah is not only an integral part of prayer but also encompasses spiritual and social dimensions that enrich the quality of worship and strengthen harmony within society. This research integrates classical and contemporary perspectives to present a synthesis relevant to the challenges of the modern era. Using a library research method and a comparative thematic tafsir approach, it analyzes Ibn Katsir’s tafsir bil-ma’tsur, which emphasizes the blessings of Basmalah, Divine justice, and sincerity in supplication, alongside Wahbah Zuhaili’s combination of bi al-ma’tsur and bi ar-ra’yi methods, which focus on monotheism (tauhid), reliance on Allah (tawakkal), and prayer as a spiritual solution. The findings reveal that Surah Al-Fatihah serves as a guide that integrates ritual, spiritual, and social dimensions, fostering profound awareness of tawhid, encouraging individual moral transformation, and creating community harmony based on Qur’anic values. In conclusion, Surah Al-Fatihah is not only foundational for ritual worship but also serves as an ethical and practical guide to enhancing worship motivation, fostering moral development, and building a harmonious and civilized society amidst modern challenges.